Overview of trends in crude palm oil production and economic impact in Malaysia - Khalida Muda; Ezerie Henry Ezechi (Program Pascasarjana Universitas Sriwijaya, 2019)
Palm oil has become a major edible and economic commodity with applications in various domestic and industrial processes. Malaysia is the second largest producer and exporter of crude palm oil (CPO). The oil palm industry in Malaysia significantly expanded and has become a major economic sector. The global demand of this precious commodity as food and fuel has caused a significant upsurge in production of oil palm. A tremendous increase of CPO production has been witnessed in the Malaysian oil palm industry over a decade now. The CPO production in 2011 was about 11.8 million tonnes but skyrocketed to 19.92 million tonnes in 2017. Beyond the revenue generation from the oil palm industry in Malaysia, there is significant investment in research and development that has resulted in the discovery of more sustainable ways to manage oil palm waste. This overview therefore seeks to evaluate the trend in crude palm oil production in Malaysia and its economic contribution to the nation from 2007-2017. Various indices associated with crude palm oil production such as planted land area, volume of exported CPO, revenue generated from the exported CPO, average annual price of exported CPO, fresh fruit yield and oil extraction rate was discussed. This overview is limited to crude palm oil production within 2007-2017 and seeks to discuss the trend within the context of the timeframe.